2014
DOI: 10.1111/aogs.12550
|View full text |Cite
|
Sign up to set email alerts
|

Achieving uterine auto‐transplantation in a sheep model using iliac vessel anastomosis: a short‐term viability study

Abstract: Internal to external iliac vessel anastomoses are an acceptable surgical technique that should be applied in a human model to ensure adequate subsequent uterine perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 19 publications
(29 reference statements)
0
33
1
Order By: Relevance
“…Each transplant procedure is referred to by a UTx number (rabbits: 3 to 9; sheep: 1 to 5) corresponding to the results described in our surgical papers. 11,12 No imaging was performed in rabbit UTx 1 or 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each transplant procedure is referred to by a UTx number (rabbits: 3 to 9; sheep: 1 to 5) corresponding to the results described in our surgical papers. 11,12 No imaging was performed in rabbit UTx 1 or 2.…”
Section: Resultsmentioning
confidence: 99%
“…Full details of the surgical procedures may be found in separate papers relating to the sheep 11 and rabbit operations. 12 …”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Saso et al investigated, developed, and evaluated anatomical, surgical, and anastomotic aspects necessary for a successful uterine transplant in a large animal model [11]. Five auto-transplants were performed in five ewes of proven fertility.…”
Section: Discussionmentioning
confidence: 99%
“…In those, at least two of the four possible anastomoses were finished, and the grafted uteri demonstrated immediate perfusion and appropriate viability 45 min post-operatively. The group concluded that internal to external iliac vessel anastomoses are an acceptable surgical technique that should be applied in a human model to ensure adequate subsequent uterine perfusion [11].…”
Section: Discussionmentioning
confidence: 99%